Las visitas a los tribunales reales: fuentes para el estudio de la conflictividad y la violencia - Inés Gómez González (Les Cahiers de Framespa)
Since the reign of the Catholic Monarchs, the Spanish monarchy has implemented a series of mechanisms for the control of the behavior of public officials. In order to regulate some institutions, especially the royal courts, the monarchy implemented visits. Usually, historians have used this source to analyze the functioning of the institutions. Analyzing the visits paid to the Chancery of Granada in the 16th and 17th centuries, this article shows that such visits are a very valuable source for the study of violence and social unrest under the Ancient Regime, especially the violence exerted by the magistrates both in their everyday life and in performing their jobs.